327 Advocating for the implementation of graduated driver licensing in the UK. (1st September 2016) - Jones, Sarah J
Abstract : Background: Although crash rates in the UK are some of the lowest in the world and are at their lowest levels ever, improvements are still possible and necessary. Analysis of crash data has shown that young drivers, aged 17 to 19 years, have crash rates that are disproportionately high when considered against the numbers of licence holders and size of the population of this age group. Description of the problem: Young drivers hold only around 2% of driving licences, but are involved in 10–16% of crashes, casualties and fatalities. Review of the evidence has shown that Graduated Driver Licensing (GDL) has successfully reduced crashes in other parts of the world, but it is not currently used in the UK. This paper discusses efforts to advocate for the implementation of GDL in the UK. Results: The project began in 2008. The author is an epidemiologist/public health specialist so, analysed UK data, with guidance from experts from New Zealand, to determine whether young drivers crashed in circumstances reasonably covered by GDL. These data, along with evidence from Cochrane reviews and primary research, were then used in presentations to raise the profile of GDL. Efforts were made to present the evidence and data as widely as possible and to engage with politicians, policy makers, policy enforcers, the media and members of the general public. Understanding political drivers, both directly and indirectly related to road safety, has been vital. It has also been important to work, and develop strong links, with other academic sectors, mainly psychology, as well as the voluntary sector. Efforts have also been made to regularly update the evidence and reanalyse the data. Conclusions: There is no simple "how to" guide to public health advocacy, nor a quick way to get things done. GDL has not yet been implemented in the UK; but it is being more widely discussed and has a higher profile than at any time previously. Advocacy takes a very long time.